DISCOURSE ANALYSIS OF PRESIDENT PRABOWO’S INAUGURAL SPEECH FOCUSING ON SYSTEMIC FUNCTIONAL LINGUISTICS AND RHETORICAL STRATEGIES - Apriyono, Teguh; Susanto, Ferri; Revola, Yashori (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates how meaning is constructed in the inaugural speech of President Prabowo Subianto through the deployment of nominalization, passivization, modality, and rhetorical strategies, and examines the communicative purposes underlying these linguistic choices in the formation of political discourse. Drawing on Systemic Functional Linguistics (SFL) and Critical Discourse Analysis (CDA), this study adopts a qualitative descriptive approach to analyze the interplay between language, power, and ideology within the speech. The findings indicate that nominalization and passivization are systematically employed to reframe processes as abstract entities and to background agency, thereby representing policies and national issues as collective responsibilities while maintaining a formal and impersonal tone. Modality, particularly expressions of obligation and high certainty, encodes authority, commitment, and determination, whereas the use of inclusive pronouns such as “we” facilitates audience alignment and collective engagement. In addition, rhetorical strategies, including repetition, parallelism, and appeals to unity, function to foreground key themes, enhance persuasive force, and construct a shared national identity. Overall, the speech operates not merely as a vehicle for articulating governmental vision but as a strategic discursive practice that legitimizes power and shapes social reality within the broader context of political leadership.